Diversity and spatial genetic structure of a natural population of Theobroma speciosum (Malvaceae) in the Brazilian Amazon - Dardengo, Juliana de Freitas Encinas (2016)
The quantification of genetic diversity and intrapopulation spatial genetic structure (SGS) of tree species are important aspects for in and ex situ conservation practices. In this study we seek to understand the importance of conservation areas by quantifying the genetic diversity and the spatial genetic structure of a natural population of Theobroma speciosum. Within this population, 49 adults and 51 subadults were genotyped for five microsatellite loci. The results showed that adults and subadults have similar levels of genetic diversity and inbreeding (adults: A= 10.4, Ae = 10.3, F= 0.68, subadults: A= 10.6, Ae= 10.6, F= 0.57). Genetic diversity was spatially structured within the population, and the results suggest that near-neighbor trees up to a distance of 70 m are likely related. SGS is likely the result of short-distance seed dispersal, the short-distance range of pollinators, and infrequent breaches of the self-incompatible mating system. Considering the high demographic density of the species and size of the study area, as well as the high average number of alleles per locus and the presence of rare alleles, we believe that the study population is an excellent resource for in situ genetic conservation of T. speciosum. The study area is also a useful resource for collecting germplasm for ex situ conservation and seed collection, either for breeding programs used in the restoration of degraded areas or forest improvement.